Between Erasure and Resistance: Precarity, Hybridity, and Vulnerability in Amitav Ghosh’s The Glass Palace - Meetu Bhatia Kapur; Rumi Roy (Transcript: An e-Journal of Literary and Cultural Studies)
Amitav Ghosh’s The Glass Palace intricately examines the nexus between precarity, hybridity, and resistance within the colonial and postcolonial landscape. The novel unravels how colonial modernity systematically displaces individuals, dismantles indigenous socio-political structures, and imposes an enduring state of vulnerability. Through its transnational characters Dolly, Rajkumar, Saya John, and Dinu Ghosh interrogate the complexities of identity, migration, and socio-economic exclusion, exposing the paradox of hybridity as both a survival strategy and a source of alienation. The narrative underscores the existential instability engendered by imperial exploitation, where economic ascent does not guarantee social acceptance, and resistance often comes at the cost of greater precarity. Moreover, the novel’s engagement with photography as a tool of historical reclamation highlights the tension between erasure and defiance, mirroring contemporary struggles against hegemonic narratives. By foregrounding the colonial production of precarity and its lingering reverberations in modern crises such as forced displacement and environmental degradation, Ghosh’s work challenges readers to confront the structures that perpetuate marginality. This paper critically examines The Glass Palace through the lens of postcolonial theory, exploring how its characters navigate the fragile space between erasure and resistance in a world where belonging is perpetually deferred.